Whole genome sequencing for M/XDR tuberculosis surveillance and for resistance testing. (March 2017) - Walker, T.M.; Merker, M.; Kohl, T.A.; Crook, D.W.; Niemann, S.; Peto, T.E.A.
Abstract: Whole genome sequencing (WGS) can help to relate Mycobacterium tuberculosis genomes to one another to assess genetic relatedness and infer the likelihood of transmission between cases. The same sequence data are now increasingly being used to predict drug resistance and susceptibility. Controlling the spread of tuberculosis and providing patients with the correct treatment are central to the World Health Organization's target to 'End TB' by 2035, for which the global prevalence of drug-resistant tuberculosis remains one of the main obstacles to success. So far, WGS has been applied largely to drug-susceptible strains for the purposes of understanding transmission, leaving a number of analytical considerations before transferring what has been learnt from drug-susceptible disease to drug-resistant tuberculosis. We discuss these potential problems here, alongside some of the challenges to characterizing the Mycobacterium tuberculosis 'resistome'—the optimal knowledge-base required for WGS-based assays to successfully direct individualized treatment regimens through the prediction of drug resistance and susceptibility in the future.